Developing the "Healthcare CEO App" for patients with type 1 diabetes transitioning from adolescence to young adulthood: A mixed‐methods study. Issue 3 (26th October 2022) - Chiang, Yueh‐Tao; Chang, Chi‐Wen; Yu, Hsing‐Yi; Tsay, Pei‐Kwei; Lo, Fu‐Sung; Chen, Chi‐Wen; Lin, Wen‐Yen; Hsu, Chien‐Lung; An, Chi; Moons, Philip
Abstract: Aim: To develop and test a mobile application that supports the disease self‐management of adolescents with type 1 diabetes during their transition to early adulthood. Design: A sequential mixed‐methods design was employed. Methods: The application content was designed according to previously identified care needs and expectations, followed by application development on the Android operating system. From the outpatient clinic of the Department of Paediatric Endocrinology and Metabolism at a medical centre in northern Taiwan, 35 individuals aged between 16–25 years participated in application testing. Results: The overall median score of the QUIS was 4–5, most of the 25% quartile was 4–5, and all of the 75% quartile was 5, indicating adequate user interaction satisfaction.